2020
DOI: 10.3892/ijmm.2020.4673
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity assessment of droplet digital PCR for SARS-CoV-2 detection

Abstract: Reverse transcription-quantitative polymerase chain reaction (RT-qPcR) is the gold standard method for the diagnosis of cOVId-19 infection. due to pre-analytical and technical limitations, samples with low viral load are often misdiagnosed as false-negative samples. Therefore, it is important to evaluate other strategies able to overcome the limits of RT-qPcR. Blinded swab samples from two individuals diagnosed positive and negative for cOVId-19 were analyzed by droplet digital PcR (ddPcR) and RT-qPcR in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
195
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 29 publications
9
195
1
Order By: Relevance
“…As of today, few studies reported the use of ddPCR for a more sensitive SARS-CoV-2 detection compared to RT-PCR 12 , 14 16 . To our knowledge, this is the first report of direct quantitation of SARS-CoV-2 RNA performed on a consistent number of clinical samples and comparing two different nasopharyngeal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…As of today, few studies reported the use of ddPCR for a more sensitive SARS-CoV-2 detection compared to RT-PCR 12 , 14 16 . To our knowledge, this is the first report of direct quantitation of SARS-CoV-2 RNA performed on a consistent number of clinical samples and comparing two different nasopharyngeal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to detect the nucleocapsid (N) gene and to use an open reading frame 1a/b (ORF1b) gene or E gene assay as a confirmatory test [3]. In addition, to improve assay sensitivity, other studies have been focusing on the detection of N, E, or ORF1b using droplet digital polymerase chain reaction (ddPCR) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…While reverse-transcriptase RT-PCR is still the gold standard, the ndings in the present study indicate that the assay sensitivity of the RT-PCR assay is reduced due to background NA from the patient sample. By contrast, the sensitivity of the RT-ddPCR multiplex assay was not affected by background NA, and is more sensitive than the gold standard reverse-transcriptase RT-PCR [4][5][6][7] in the clinical setting.…”
Section: Discussionmentioning
confidence: 89%
“…Another approach is to detect the nucleocapsid (N) gene, and to use an open reading frame 1a/b (ORF1b) gene or E gene assay as a con rmatory test [3]. In addition, to improve assay sensitivity, other studies have been focusing on the detection of N, E or ORF1b using droplet digital polymerase chain reaction (ddPCR) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%